"DOST" Model to Link and Support Drug Resistant TB Patients From Private Sector: An Experience From Delhi, India - Vindhya Vatsyayan; Theresa Pattery; Khasim Sayyad; Jason Williams; Arnab Pal; Vikas Panibatla; Ashwani Khanna (Frontiers Media S.A., 2022)
BackgroundThe National TB Elimination Programme (NTEP) has quite successfully involved private sector for referral of presumptive drug resistant TB (DR-TB) patients for molecular testing and referral for DR-TB management. There was a challenge as all the referred patients were not reaching to the facilities. A "DOST" intervention model was implemented to strengthen the patient care pathway. We conducted this study to describe the patient care cascade, the clinico-demographic characteristics of patients linked to the treatment and to estimate the mean turn-around time for drug resistant TB care services.MethodsIt is a cross-sectional study conducted at New Delhi during the period July 2019-December 2020 under programmatic settings.ResultsA total of 9,331 patients were subjected to CB-NAAT test and 382 (4%) were found to be resistant for rifampicin and 231 (76%) were initiated on treatment in the public sector under NTEP.ConclusionThe DOST intervention model developed to link the DR-TB patients from private sector to the public sector DR-TB centers is found to be efficient and effective.